Wrestling the Hulk : my life against the ropes - Hogan, Linda, 1959- (William Morrow, 2011)
The former wife of the American wrestling icon describes her life with The Hulk and reveals how she survived her experiences with abuse, infidelity, and fame to embrace her new single status.